Understanding repertoires of pedagogical practices and multiliteracies in Chilean schools: how to connect content and experience for learning - Thibaut, Patricia; Lizasoain, Andrea; Lira-Muñoz, Ninoska (Frontiers in Communication, 2025)
IntroductionWe live in a context of cultural and linguistic diversity enhanced by the ubiquity of digital technology. This environment enables greater diversity in the way we construct meaning, make sense of the world and project identities, which challenges educational institutions to prepare new generations for the future. Studies have pointed to the importance of expanding pedagogical repertoires in the classroom and new ways of meaning-making. However, more research is needed in order to move beyond this analysis.MethodsThis qualitative study seeks to contribute to this research gap, by analyzing two Chilean schools with the objective of understanding the relationship between knowledge processes, types of modes used in the classroom and pedagogical repertoires. The methodology included the observation of 975 min of 12 language (Spanish) classrooms-grades 6th, 7th and 8th-in a rural and urban school, and interviews with teachers conducted at various moments of data collection. Data were analyzed through a mixed-methods approach.ResultsThe results suggest that there is a dissonance between the pedagogy of multiliteracies and the observed pedagogical and modality repertoires. The results show a predominance of traditional pedagogical practices in the Chilean classroom focused on conceptualization and, to a lesser extent, critical analysis through conventional modes such as written text and oral language.DiscussionConsequently, to move beyond traditional models, such as those observed in this study, emphasis should be placed on teaching semiotic modes that depart from the classical canon both in initial training and continuing professional development as well as on teaching pedagogical repertoires focused on contextualization and application. In this way, there would be a stronger balance between the cognitive, socio-emotional and embodied domains in the classroom. Therefore, experienced and functional pedagogy should have greater visibility, which is also related to the use of a greater variety of modes in educational contexts.